408 WS Distinguished Service Talk: Effects of steam flaking on the carbon-footprint of finishing beef cattle. (30th November 2020) - Cole, N A; Parker, David B; Brown, Mike S; Jennings, Jenny S; Hales, Kristen E; Gunter, Stacey A
Abstract: Grain processing has been used for many decades to improve the digestibility of feed grains fed to finishing beef cattle and to improve animal performance. The most common methods currently used by feedyards in the U.S. are dry rolling (DRC) and steam flaking (SFC). However, the environmental effects of gain processing have not been rigorously studied. This manuscript presents a comparative estimate of the carbon footprint of steam flaking corn in beef cattle finishing diets with and without wet distiller's grains with solubles (WDGS). Estimates were based on results of published literature and the Intergovernmental Panel on Climate Change. Although SFC required more natural gas and electricity for processing than DRC, feeding SFC decreased the total carbon-footprint by 9 to 13 % per steer. This was primarily due to 30% lower enteric methane production, 13% lower manure nitrous oxide emissions, and 8% lower feed production requirement than when DRC was fed. The carbon-footprints were slightly greater when the diet contained 20% WDGS than when it contained 0% WDGS.